Design and Build A Smart Book Cabinet Prototype Using Arduino And Smartphone - Satria, Habib; Nainggolan, Marco Polo; Mungkin, Moranain; Sembiring Maha, Denny Hasminta (Universitas Harapan Medan, 2024)
In the current digital era, managing books and print media is still a challenge for many individuals. In an effort to overcome this problem, this research proposes a Smartbook Cabinet design that combines Arduino and smartphone technology. This Smartbook Cabinet aims to simplify the management and search for books more efficiently. This Smartbook Cabinet is equipped with a QR code-based book marking system which is connected to a smartphone application. By using a smartphone, users can scan the QR code on each book they want to find or. Arduino acts as the brains of this system, coordinating interactions between the bookshelf and the smartphone app. The results of this research show that the Smartbook Cabinet can increase efficiency in book management and provide easy access to users. Users can quickly find the books they are looking for via the smartphone application, and the book condition monitoring system will keep the book collection well maintained. Thus, this Smartbook Cabinet provides an innovative solution for smarter and more efficient book management, utilizing Arduino and smartphone technology to achieve this goal.